Exploring levels and factors associated with transition challenges for Syrian refugee parents resettled in Canada - Hala Tamim; Elena Levitskaya; MacGregor Goodman; Gwen Ehi; Aliza Maqsood; Safoura Zangiabadi; Yunis Khaled (PLoS ONE, 2025)
Although the literature has documented numerous challenges Syrian refugees face during their resettlement in Canada, the unique transition experiences of Syrian refugee parents remain underexplored. This study examines demographic, community and social, migration, and health-related factors that influence the level of difficulty experienced by Syrian refugee parents in Canada during their transition. This cross-sectional, interview-based study was conducted from March 2021 to March 2022, involving 540 Syrian refugee parents in Ontario with at least one child under the age of 18. Transition difficulty was measured based on the question “How difficult has the transition into Canada been for you?” Responses ranged from 1 representing “Not difficult at all” and 5 representing “Very difficult”. 6.5% of participants rated their transition as “Not difficult at all”, 15.9% as “Not difficult, “20.6% as “Neutral”, 43% as “Difficult”, and 13.7% as “Very difficult”. Results of the multiple linear regression analyses indicated that greater transition difficulty was significantly associated with experiences of discrimination at children’s school events (Adjβ = 0.138, p = 0.038), dissatisfaction with friendships (Adjβ = 0.134, p = 0.006), being over age 45 (Adjβ = 0.301, p = 0.047), lower proficiency in English or French (Adjβ = − 0.145, p = 0.008), longer duration spent in Canada (Adjβ = 0.123, p < 0.001), Blended Visa Office-Referred program (Adjβ = 0.530, p = 0.026) and poorer mental health (Adjβ = 0.173, p < 0.001). The findings from this study highlight the need for policies and frameworks aimed at improving resettlement efforts for refugee parents, thereby promoting the overall well-being of Syrian refugee families in Canada.